Interleukin-5 Mediates Parasite-Induced Protection against Experimental Autoimmune Encephalomyelitis: Association with Induction of Antigen-Specific CD4+CD25+ T Regulatory Cells - Tran, Giang T.; Wilcox, Paul L.; Dent, Lindsay A.; Robinson, Catherine M.; Carter, Nicole; Verma, Nirupama D.; Hall, Bruce M.; Hodgkinson, Suzanne J. (Frontiers in Immunology, 2017)
Objective. To examine if the protective effect of parasite infection on Experimental Autoimmune Encephalomyelitis (EAE) was due to interleukin-5, a cytokine produced by a Type-2 response that induces eosinophilia. We hypothesise that in parasite infections IL-5 also promotes expansion of antigen-specific T regulatory cells that control autoimmunity. Methods. Nippostrongylus brasiliensis larvae were used to infect Lewis rats prior to induction of EAE by myelin basic protein. Animals were sham-treated, or given blocking monoclonal antibodies to interleukin 4 or 5 or to deplete CD25+T cells. Reactivity of CD4+CD25+T regulatory cells from these animals was examined. Results. Parasite infected hosts had reduced severity and length of EAE. The beneficial effect of parasitic infection was abolished with an anti-IL-5 or an anti-CD25 monoclonal antibody, but not anti-IL-4 monoclonal antibody. Parasite infected animals with EAE developed antigen-specific CD4+CD25+T regulatory cells earlier than EAE controls and these expressed more Il5ra than controls. Treatment with IL-5 also reduced the severity of EAE and induced Il5ra expressing CD4+CD25+T regulatory cells. Interpretation. The results of this study suggested that IL-5 produced by the Type-2 inflammatory response to parasite infection promoted induction of autoantigen-specific CD25+Il5ra+T regulatory cells that reduced the severity of autoimmunity. Such a mechanism may explain the protective effect of parasite infection in patients with multiple sclerosis where eosinophilia is induced by IL-5, produced by the immune response to parasites.